THE EFFECT STOCK LIQUIDITY TO CASH DIVIDEND FOR NON-FINANCE COMPANY LISTED ON BEI IN 2012 - 2016 - Arif Herlambang; Putu Anom Mahadwarta; Stefan Adi Christianto (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
This research aims to analyze factors of stock liquidity, size, profitability, growth, leverage, and cash which affect cash dividend. Independent variable such as stock liquidity, size, profitability, growth, leverage, and cash which affect cash dividend. This research use quantitative approach by using multiple linier regression. The sample of this research is the non-financial company that listed in IDX (Indonesia Stock Exchange) for period of 2012 to 2016. Final samples which are used in this research were 78 business entities with 390 observations. Based on this research, the result show that stock liquidity, and growth give positive effect to cash dividend. size, profitability, leverage, and cash give negative effect to cash dividend.